Air-broadened N2O line-shape parameters and their temperature dependences by requantized classical molecular dynamics simulations. (June 2021) - Ngo, N.H.; Nguyen, H.T.; Le, M.T.; Tran, H.
Highlights: Air-broadened N2 O line shapes were calculated using requantized classical molecular dynamics simulations. The simulated spectra were fit with various line-shape models which include the first-order line mixing, providing the corresponding line-shape parameters for J′′ ≤ 59. The temperature dependences of line-shape parameters were also deduced. Comparisons with available experimental values show good agreements. Abstract: In this paper, we used requantized Classical Molecular Dynamics Simulations (rCMDS), corrected by the room temperature air-broadening coefficients measured in the ν3 band of N2 O, to predict line-shape parameters including the broadening coefficient, its speed dependence component, the Dicke narrowing and the line-mixing coefficients, associated with various line-shape models for air-broadened N2 O absorption lines. For that, we first computed the auto-correlation functions of the N2 O dipole moment, responsible for the absorption transitions. The Fourier-Laplace transform of these functions directly yields the absorption spectra. Calculations were made for three temperatures 200, 250 and 296 K and 1 atm of N2 O/air mixtures and for a large range of values of the ratio between the Doppler and Lorentzian widths. The obtained spectra were then fitted with the quadratic speed-dependent Voigt profile including the first-order line mixing using a multi-spectrum fitting procedure. Comparisons with values determined from room temperature high-precision measurements in the ν3 band of N2 O by using the same profile [Loos et al, J. Quant. Spectrosc. Rad. Transf., 151, 2015, 300-309] show that our retrieved line broadening coefficients are overestimated by about 4%. The difference between the measured and predicted line broadening coefficients was used to empirically correct the rCMDS auto-correlation functions and thus the corresponding absorption spectra. These latter were then fitted with the Voigt, the speed-dependent Voigt, and the speed-dependent Nelkin-Ghatak profiles, all of them being associated with the first-order line-mixing approximation, providing the corresponding line-shape parameters for lines up to J′′ ≤ 59. The temperature dependences of various line-shape parameters were also deduced. The results show a very good agreement with available experimental data for all the considered parameters.